History and Evolution of Sustainability Reporting: From Initiation to Standardized Practices - Elena STĂNCIULESCU (CECCAR Business Review)

(untitled)
The idea of sustainability has its roots in the awareness that the Planet’s natural resources are finite and that uncontrolled economic development can have negative effects on the environment and society. In this article, we aim to investigate the evolution of sustainability, as it helps us better understand how the current standards in this field have emerged, why they are necessary, and how we can build responsible strategies that meet the demands of modern society and protect resources for future generations.